The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/1471-0307.12278
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, rheological and sensory properties of Egyptian Kariesh cheese containing wheat bran

Abstract: The physicochemical, rheological and sensory properties during the storage of Kariesh cheeses made with 0.1, 0.2, 0.3, 0.4 or 0.5 g wheat bran/100 g milk were evaluated at 0, 7 and 15 days. The cheeses with 0.5 g wheat bran/100 g milk had a significantly (P < 0.01) higher yield and moisture content, and lower pH and protein content than the control. No significant differences (P > 0.01) in salt and ash contents were observed among the cheeses studied. Texture profile analysis showed that the rheological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
4
8
0
Order By: Relevance
“…This indicated that the increase in yield might be due to the presence of fiber in karish cheese made by mushroom mycelium. Similar finding was previously found by other authors (Ahmed et al, 2005;Abd El-Hamid et al (2016); Zayan, 2016;Basiony et al, 2018). Onwulats (2008) found that dietary fiber absorbed water from the environment.…”
Section: Yield Of Karish Cheesesupporting
confidence: 91%
See 1 more Smart Citation
“…This indicated that the increase in yield might be due to the presence of fiber in karish cheese made by mushroom mycelium. Similar finding was previously found by other authors (Ahmed et al, 2005;Abd El-Hamid et al (2016); Zayan, 2016;Basiony et al, 2018). Onwulats (2008) found that dietary fiber absorbed water from the environment.…”
Section: Yield Of Karish Cheesesupporting
confidence: 91%
“…This might be attributed to the growth of the starter bacteria and produced lactic acid. Similar results were obtained by Abd El-Hamid (2016) for wheat bran supplemented karish cheese.…”
Section: Titratable Acidity During Coagulation Of Karish Cheese Samplessupporting
confidence: 89%
“…The addition of GPP modified the sensory attributes of cheeses. Generally, the addition of fibers or by-products exert a strong effect on the sensory parameters of dairy products [ 37 , 52 ]. In this study, except for sweet and bitter that scored similar values in all trials, all other attributes evaluated were consistently influenced by the addition of GPP.…”
Section: Resultsmentioning
confidence: 99%
“…The less soluble samples like Br-SC, Art-SC, and the two grape pomace powder cheeses investigated were also the least juicy (scores from 3 to 4.5). In the literature, several examples of the effects of the water binding capacity of by-products on texture parameters and tactile sensation when incorporated into different foods (i.e., bakery, dairy, and meat products) have been reported [ 11 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Marchiani et al [ 10 ] assessed the physicochemical and nutritional quality of grape pomace powder to fortify semi-hard cheese. Abd Elhamid [ 11 ] proposed the incorporation of wheat bran in Kariesh cheese.…”
Section: Introductionmentioning
confidence: 99%